Pengaruh Pemberian Informasi Terhadap Tingkat Pengetahuan Hipertensi Pada Calon Jemaah Haji Kota Batu Tahun 2023 - Indrawan, Doby; Anwari, Dhiaz Taupiq (Journal of Islamic Medicine, 2025)
Background: Hypertension is a highly prevalent condition among Indonesian Hajj pilgrims, serving as a critical risk factor for cardiovascular diseases, the leading cause of mortality during the pilgrimage. Knowledge of hypertension plays a pivotal role in promoting healthy behaviors and lifestyles essential for its prevention. This study examines the relationship between the provision of targeted information and the improvement of knowledge levels among prospective Hajj pilgrims in Batu City in 2023. Objective: To analyze the impact of educational interventions on the hypertension knowledge levels of prospective pilgrims in Batu City. Methods: A pretest-posttest design was employed on 63 respondents selected using consecutive sampling. Interventions included counseling sessions and distribution of leaflets focusing on hypertension awareness. Changes in knowledge levels were assessed by comparing pretest and posttest scores, with data analyzed using the Mann-Whitney test. Results: The findings revealed a statistically significant improvement in knowledge levels (p = 0.003). Mean pretest scores increased from 78.22 to a posttest mean of 82.92. Respondents demonstrated notable improvement across multiple knowledge domains, indicating the efficacy of the intervention. Conclusion: Providing targeted educational information significantly enhances knowledge about hypertension among prospective Hajj pilgrims in Batu City. This emphasizes the critical role of tailored health education in preparing pilgrims for the physical and health challenges of the pilgrimage.